Dense Reduced Graphene Oxide Films Obtained by Pressing Create Stable and Compact Capacitive Energy Storage. Issue 9 (14th April 2020) - Lin, Dou; Tang, Zihui; Pan, Qijun; Zhang, Shiping; Huo, Dexian; Yan, Sisi; Han, Fangming
Abstract: It is generally believed that the re‐stacking of reduced graphene oxide (rGO) sheets limits the electrochemical energy storage. Therefore, rGO based electrodes are usually designed to be non‐compact porous and fluffy structures. However, fluffy structures could reduce the conductance, structure stability, and cycling stability of electrodes. Here, to balance the contradiction, three electrodes with different compactness were studied. Amazingly, dense rGO hydrogel films (DrGO‐HF) achieved by simply pressing filtrated rGO films, show highly stable (92 % capacitance retention after 250 000 cycles) and high‐performance compact capacitive energy storage, which can be attributed to the structural stability and electrical conductivity enhanced by the close contact between graphene sheets. This study clarifies the scientific fact that the re‐stacking of rGO sheets would not degrade the electrochemical energy storage performances, which is of great significance for the design and preparation of supercapacitor electrodes with high volumetric energy density. Abstract : Out with the fluff, in with the tough : Dense reduced graphene oxide hydrogel films (DrGO‐HFs) are achieved by simply pressing a filtrated rGO film, showing highly stable and high‐performance compact capacitive energy storage, which reveals that dense rGO has more potential than fluffy rGO as an excellent electrochemical energy storage electrode.